A contribution to a multidimensional analysis of trade competition - Moreira, S.; Simões, N.; Crespo, N. (The World Economy, 2017)
International trade grew substantially throughout the last decades and international relations became more important for the economic performance of the countries. Simultaneously new poles emerged in the international arena leading to growing competition for higher market shares. Therefore, trade competition is a critical dimension of analysis for applied international trade studies. We propose a conceptual framework for measuring this phenomenon by combining some critical previous contributions to build a multidimensional and more comprehensive concept, which defines trade competition as a function of the degree of both structural similarity and total exports overlap. Moreover, structural similarity should take into account three elements: sectoral shares similarity, inter-sectoral similarity (evaluating how different the distinct sectors are), and intra-sectoral similarity (proximity in terms of quality ranges exported). Several measures are proposed to empirically capture the concept suggested. Finally, we present an example including the exports of six European economies (Germany, France, the United Kingdom, Greece, Hungary, and Sweden) to 124 destination markets (in 2007, 2011, 2015) in order to illustrate the application of the concept and measures suggested.